Specification, Design and Evaluation of an Automated Agrochemical Traceability System - Peets, Sven (Cranfield University, 2009)
Traceability through all the stakeholders in food production is an issue of increasing importance, being specifically required by the regulations for food safety and quality (EC 178/2002), and for compliance with environmental protection. The agricultural market perceives a need for systems and technologies to automate the currently manual process of producing records of agrochemical inputs loaded into a spraying machine. A novel prototype Automated Agrochemical Traceability System (AACTS) to identify and weigh agrochemicals as they are loaded into crop sprayer has been designed, constructed, fitted to a machine and evaluated with commercial operators. The functional blocks of the system are a 13.56 MHz RFID reader, 1.4 litre self cleaning weighing funnel mounted on a 3 kg load cell, a user interface with a screen and three user command buttons (Yes, No, Back), and a progress bar made of 8 coloured LED’s (green, amber, red). The system is able to trace individual agrochemical containers, associate the product identity with national agrochemical databases, quantify the required amount of product, assist the sprayer operator and control workflow, generate records of sprayer inputs and interoperate with (recommending extensions to) task management standards as set out in ISO 11783-10. The evaluation of the quantity weighing has demonstrated that with such a system, the principal noise component is in the range of 33–83 Hz, induced by the operating tractor engine. A combined 3 Hz low pass digital filter with a second stage rolling mean of 5 values improves performance to allow a practical resolution of 1 gram (engine switched off) to 3.6 grams (sprayer fully operational) with a response appropriate to suit human reaction time. This is a significant improvement over the ±10 grams of the work of Watts (2004). An experiment with 10 sprayer operators has proved that in the majority of cases (92%) an accuracy equal or better than ±5% is achieved regardless of dispensing speed. The dispensed amounts (100.36% of target) and recorded (100.16%) are in accordance with prescribed values (100%; LSD(5%) 2.166%), where amounts dispensed by manual methods (92.61%) differ significantly from prescribed and recorded value (100%). The AACTS delivers a statistically similar work rate (211.8 s/task) as manual method (201.3 s/task; Δt = 10.5 s/task; LSD(5%) 28.2 s/task) in combined loading and recording cycle. Considering only the loading time (181.2 s/task) of manual method, the difference is 30.6 s/task (LSD(5%) 30.1 s/task). In practice this difference is believed to be marginal compared to the time required to load the water, random external events during the spraying session and in time moving, checking and storing paper records. The integrated weighing funnel concept is another significant improvement over previous work. Using this system, the mean duration of measuring per container for all tasks (34.0 s) is approximately half the time (68.5 s) achieved by Watts (2004). The AACTS was rated to be safer than the manual method regarding operator health and safety and risk of spillage. All operators who evaluated the AACTS were interested in purchasing such a system. The work confirmed that an RFID system was an appropriate media for agrochemical identification performing more than 250 product identification operations during operator tests without failure, with a speed of operation <1 s per cycle and reading distance of 100 mm. A specific format for RFID tag data is proposed for adoption, using low cost tags, that combines item level traceability with identification of products independently without access to worldwide databases. The AACTS follows ISO 11783 task management logic where a job is defined in a prepared electronic task file. It is proposed to extend the ISO 11783-10 task file to integrate the records provided by AACTS by handling the tank loads as individual products resulting from loading task and allocating them to spraying tasks. It is recommended to produce a production prototype following the design methodology, analysis techniques and performance drivers presented in this work and develop the features of user interface and records of tank content into software for ISO 11783-10 cabin task controller to deliver business benefits to the farming industry. The results with RFID encourage the adoption of RFID labelling of agrochemical containers. The reader may wish to read this thesis in parallel with Gasparin (2009) who has considered the business and industry adoption aspects of the AACTS.